Atypical hemolytic uremic syndrome triggered by varicella infection. (2017) - Condom, Pauline; Mansuy, Jean-Michel; Decramer, Stéphane; Izopet, Jacques; Mengelle, Catherine
Abstract: Varicella Zoster Virus (VZV) is a well-known virus that belongs to the Herpesviridae family which induces a self-limited disease except in specific cases in particular among stem cell transplant patients. This virus is not known however to trigger atypical Hemolytic Uremic Syndrome (aHUS). Here we report the case of a six-year-old boy who was hospitalized with fever and abdominal pains associated to pruritic and vesicular rash, thrombocytopenia and acute renal failure. He was diagnosed with aHUS precipitated by varicella virus. He was treated by an association of antimicrobials against potential superinfections, plasmapheresis and eculizumab for curative aHUS treatment. This was effective but after 6 months the kidney function remained poor. The current case describes an aHUS associated to varicella infection as demonstrated by the simultaneous occurrence of the viral infection and aHUS manifestations. Apart from typical Hemolytic Uremic Syndrome which is triggered by bacteria mostly Shiga toxin producing Echerichia coli and Streptococcus pneumoniae or Shigella, aHUS may be linked to viral infections such as HIV, EBV and enteroviruses, but very rarely by varicella. This case highlights a possible even rare complication of varicella infection a very common childhood disease. This complication could be avoided by to anti-VZV vaccination.